Fatores determinantes da ocorrência de tuberculose no Norte de Minas Gerais - Magalhães, Sandra Célia Muniz (2013)
The resurgence of some diseases depends on space organization, that is, some areas are more prone to disease occurrence, but the way in which public policies are implemented, may lead to the occurrence of situations propitious to the emergence or resurgence of diseases such as tuberculosis, which has caused great concern to the healthcare industry. Throughout history in the North and Northeast regions of Brazil, including the North of Minas Gerais, the lack of implementation of public policies to reduce inequalities and inequities in health and improve the living conditions of the population explains perfectly the persistence of tuberculosis. The main goal of this research was to understand the determining factors in the occurrence of tuberculosis in Northern Minas Gerais, evaluating access to health services and social and spatial conditions of the carriers. The research methodology consisted of documentary and bibliographical, mappings, field observation with questionnaires and interviews with tuberculosis patients on treatment in the municipalities of Montes Claros and Miravânia and interviews with managers of the epidemiology of Health Regional Superintendence of Montes Claros and The Health Regional Management of Januária and Pirapora. The survey results indicate that the higher incidence of tuberculosis in the Northern Minas was in Montes Claros and Miravânia respectively. Montes Claros considered the pole town of The North, having a very significant population growth, which demands expansion of drinking water services; sewage collection and treatment; proper collection and disposal of garbage; expansion of land use; urban drainage and other services necessary for the improvement of the quality of urban life. However all of these services are insufficient and cause loss to users. Miravânia is a predominantly rural municipality with a low purchasing power population, therefore very bad living conditions. The difficult access to basic health services of the population is the main factor which contributes to difficult tuberculosis control in the North of Minas. Anyway, the improvement of the living conditions of the population in the northern region of Minas Gerais will be the main instrument or strategy to fight tuberculosis in the region. Investments in actions such as sanitation, housing quality, employment, income, education and other mechanisms that enable major and lasting social transformation will be essential in this sense.